2009
DOI: 10.4012/dmj.28.89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of application time and agitation for bonding orthodontic brackets with two self-etching primer systems

Abstract: The purpose of this study was to evaluate the shear bond strength, adhesive remnant index (ARI) and etching effect of two self-etching systems (Transbond Plus, Beauty Ortho Bond) at different application times (3, 10, 30 seconds) with and without agitation. Share bond strengths were examined and the ARI score was estimated (n=15). Enamel surfaces after priming were examined by SEM. Increasing application time and applying agitation of self-etching primers produced slightly increased etching efficacy. Increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The bonded area established in this experiment was equivalent to one-third of one bracket section. Several researchers have described residual adhesive levels after debracketing, at various bond strengths (20)(21)(22)(23). Rikuta et al (24) reported that an area of more than 50% of the SB, which was used to bond the metal bracket onto the tooth surface in a shear test, occurred in 90% of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The bonded area established in this experiment was equivalent to one-third of one bracket section. Several researchers have described residual adhesive levels after debracketing, at various bond strengths (20)(21)(22)(23). Rikuta et al (24) reported that an area of more than 50% of the SB, which was used to bond the metal bracket onto the tooth surface in a shear test, occurred in 90% of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, the SBS values for all groups were greater than the 6 to 8 MPa estimated by Reynolds to be necessary in orthodontic treatment 26) . Although self-etching is clinically acceptable, it produces weaker bonds compared to phosphoric acid etching [27][28][29] . The findings of the present study are further corroborated by the results of Elekdag-Turk et al 36) .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the strength of self-etching primer systems 15,18,19,[23][24][25][26][27][28][29][30][31][32][33] . Most of these studies demonstrated that self-etching systems have significantly lower SBS values than conventional acidetching systems 18,24,26,34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In addition to saving time and reducing procedural errors with such a primer, their lower etching ability, due to their higher pH compared to phosphoric acid, might minimize enamel loss. [7][8][9][10] Previous studies have reported the effects of the acidity, 11,12 application time, [13][14][15][16] and agitation [14][15][16] on etching efficacy.…”
Section: Introductionmentioning
confidence: 99%